1991
DOI: 10.1086/132870
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of seeing on a 62-cm mirror

Abstract: A 62-cm active optics telescope model with a Shack-Hartmann wavefront analyzer was used to measure the mirror seeing effect. The degradation of the imaging quality due to the generation of microthermal convection was quantitatively evaluated from diurnal monitoring measurements over 90 days and nights. The dependence of mirror seeing on the temperature difference between the mirror and the ambient air and the effect of flushing flow to blow away the microthermal turbulence were measured.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…Our fit predicts that we obtain an additional 41.6 ± 1.2 nm of wavefront error when M1 is 3 • C warmer than the outside air. This behavior is consistent with results from previous studies of mirror seeing [25][26][27] when ∆T M > 0 • C. Past studies observed a weaker effect at ∆T M < 0 • C. Our data are consistent with an equal slope at both warmer and cooler temperatures, although hints of a weaker effect at cooler temperatures are present. We note that our data span a larger range of negative temperatures than most previous studies.…”
Section: Effect Of Temperature Differentials On Residual Wavefront Ersupporting
confidence: 93%
“…Our fit predicts that we obtain an additional 41.6 ± 1.2 nm of wavefront error when M1 is 3 • C warmer than the outside air. This behavior is consistent with results from previous studies of mirror seeing [25][26][27] when ∆T M > 0 • C. Past studies observed a weaker effect at ∆T M < 0 • C. Our data are consistent with an equal slope at both warmer and cooler temperatures, although hints of a weaker effect at cooler temperatures are present. We note that our data span a larger range of negative temperatures than most previous studies.…”
Section: Effect Of Temperature Differentials On Residual Wavefront Ersupporting
confidence: 93%
“…The seeing contributed by a 3.5 m primary mirror warmer than the air outside the dome can range from 0.4 to 0.6 arcsec per Celsius degree (Zago 1986;Racine et al 1991), a value which is comparable or higher than the natural seeing in good astronomical sites. Several laboratory studies of image deterioration by convection (Lowne 1979;Iye et al 1991) confirm that microthermal activity grows significantly as soon as the temperature gradient between dome air and primary mirror is positive. The dome itself is a major source of seeing degradation (Bely 1987), and the seeing contribution is highly variable, depending on the telescope enclosure design.…”
Section: Introductionmentioning
confidence: 98%
“…In order to develop active optics, a prototype telescope has been made at the National Astronomical Observatory of Japan with a monolithic 61-cm diameter 2.1-cm thick primary pyrex mirror [4]. The shape of the mirror was controlled by 12 actuators.…”
Section: Effect Of Telescope Mirror Thermal Condition On Degradation ...mentioning
confidence: 99%
“…Turbulence is usually characterized by the Rayleigh number. However, in our case a component of the Rayleigh number, the Brunt-Väisälä frequency [4], can be used as an objective characteristic of turbulence:…”
Section: Effect Of Telescope Mirror Thermal Condition On Degradation ...mentioning
confidence: 99%